Disgraced pedologists (Training and Practice : Journal of Educational Sciences, 2020)
This study focuses on the short analyses of some prominent Soviet–Russian pedologists’ walk of life – such as Behtyerev, Blonszkij, Nyecsajev, Baszov, Vigotszkij and Zalkind’s – and on the introduction of their successes and failures in the field of science. In the 1920s, pedology was an important part of the Soviet–Russian education. In the 1930s, when Stalinism emerged, what impact did the political decisions against pedology and pedologists have on their personal lives? We attempt to explore the political background why the pedologists became disgraced. In our biographical analysis, we pay special attention to the reasons for the elimination of pedology, their field of study and its effect on the development of special education in the Soviet– Russian context.